Closed incision negative pressure wound therapy versus standard dressings in obese women undergoing caesarean section: multicentre parallel group randomised controlled trial. (5th May 2021) - Gillespie, Brigid M; Webster, Joan; Ellwood, David; Thalib, Lukman; Whitty, Jennifer A; Mahomed, Kassam; Clifton, Vicki; Kumar, Sailesh; Wagner, Adam; Kang, Evelyn; Chaboyer, Wendy
Abstract: Objective: To determine the effectiveness of closed incision negative pressure wound therapy (NPWT) compared with standard dressings in preventing surgical site infection (SSI) in obese women undergoing caesarean section. Design: Multicentre, pragmatic, randomised, controlled, parallel group, superiority trial. Setting: Four Australian tertiary hospitals between October 2015 and November 2019. Participants: Eligible women had a pre-pregnancy body mass index of 30 or greater and gave birth by elective or semi-urgent caesarean section. Intervention: 2035 consenting women were randomised before the caesarean procedure to closed incision NPWT (n=1017) or standard dressing (n=1018). Allocation was concealed until skin closure. Main outcome measures: The primary outcome was cumulative incidence of SSI. Secondary outcomes included depth of SSI (superficial, deep, or organ/body space), rates of wound complications (dehiscence, haematoma, seroma, bleeding, bruising), length of stay in hospital, and rates of dressing related adverse events. Women and clinicians were not masked, but the outcome assessors and statistician were blinded to treatment allocation. The pre-specified primary intention to treat analysis was based on a conservative assumption of no SSI for a minority of women (n=28) with missing outcome data. Post hoc sensitivity analyses included best case analysis and complete case analysis. Results: In the primary intention to treat analysis, SSI occurred in 75 (7.4%) women treated with closed incision NPWT and in 99 (9.7%) women with a standard dressing (risk ratio 0.76, 95% confidence interval 0.57 to 1.01; P=0.06). Post hoc sensitivity analyses to explore the effect of missing data found the same direction of effect (closed incision NPWT reducing SSI), with statistical significance. Blistering occurred in 40/996 (4.0%) women who received closed incision NPWT and in 23/983 (2.3%) who received the standard dressing (risk ratio 1.72, 1.04 to 2.85; P=0.03). Conclusion: Prophylactic closed incision NPWT for obese women after caesarean section resulted in a 24% reduction in the risk of SSI (3% reduction in absolute risk) compared with standard dressings. This difference was close to statistical significance, but it likely underestimates the effectiveness of closed incision NPWT in this population. The results of the conservative primary analysis, multivariable adjusted model, and post hoc sensitivity analysis need to be considered alongside the growing body of evidence of the benefit of closed incision NPWT and given the number of obese women undergoing caesarean section globally. The decision to use closed incision NPWT must also be weighed against the increases in skin blistering and economic considerations and should be based on shared decision making with patients. Trial registration: ANZCTR identifier 12615000286549.